The Measurement of emotions - Plutchik, Robert; Kellerman, Henry (Emotion, theory, research, and experience, 1989)
Emotion: Theory, Research, and Experience, Volume 4: The Measurement of Emotion provides an examination of the key issue of how to measure emotion. The book contains articles that present different approaches to the study of emotional measurement. Contributors focus on such topics as mood measurement; cross-cultural examination of triggers of emotion; possible dimensions that underlie the language of affect; measurement of emotions in lower animals; and measuring emotions and their derivatives. Psychologists, psychiatrists, behavioral psychologists, teachers, and students will find the book a.